A Mathematical Network Model and a Solution Algorithm for IaaS Cloud Computing - Colajanni, Gabriella; Daniele, Patrizia (Networks and spatial economics, 2022)
Cloud Computing is a type of Internet-based computing, much used in recent years, that relies on sharing computer processing resources and data to computers and other devices on demand, from any location and at any time rather than having local servers or personal devices to handle applications. This shared IT infrastructure contains large pools of systems that are linked together. Often, virtualization techniques are used to maximize the power of cloud computing. In this paper we describe the global network of a cloud computing environment with five different layers, represented by hardware/datacenter, infrastructure, platform, application and end-users. Then, we present the mathematical model of the network and study the behavior of the typical IaaS provider in order to find the optimization problem. A computational procedure for the calculus of the optimal solutions is proposed, is applied to two numerical examples and is compared with a linearization.